2020
DOI: 10.1002/ijc.32934
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of late concurrent hypofractionated radiotherapy in advanced melanoma patients failing anti‐PD‐1 monotherapy

Abstract: Advanced melanoma patients who failed anti‐PD‐1 therapy have limited options. We analyzed a cohort of 133 advanced melanoma patients receiving anti‐PD‐1 monotherapy in a referral center between April 2015 and December 2017, and included the 26 patients with confirmed progressive (PD) or stable disease who received additional radiotherapy with an unmodified anti‐PD‐1 mAb regimen. Tumor evaluations were done on radiated and nonradiated (RECIST 1.1) lesions, with abscopal effect defined as a partial (PR) or compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…There has been a systematic review that reported that the mean incident for an distant/abscopal response was 41% in 1736 non-small-cell lung cancer patients treated with an ICIs-SABR combination [ 44 ]. However, some investigators argued that this so-called distant response of non-irradiated lesions cannot be called a real abscopal response, since ICIs are systemic broad-spectrum anti-tumor drugs [ 45 ]. Thus, these patients may have a systemic anti-tumor effect, even if they were not irradiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a systematic review that reported that the mean incident for an distant/abscopal response was 41% in 1736 non-small-cell lung cancer patients treated with an ICIs-SABR combination [ 44 ]. However, some investigators argued that this so-called distant response of non-irradiated lesions cannot be called a real abscopal response, since ICIs are systemic broad-spectrum anti-tumor drugs [ 45 ]. Thus, these patients may have a systemic anti-tumor effect, even if they were not irradiated.…”
Section: Discussionmentioning
confidence: 99%
“…The real abscopal effect should be defined as treatment of ICIs being ineffective, and the irradiation of major or progressive lesions can mediate tumor regression at a remote site. Recently, Elisa Funck-Brentano et al [ 45 ] reported a retrospective study that correctly analyzed the abscopal effect, in which 26 melanoma patients who failed anti-PD-1 monotherapy were included. The abscopal effect was seen in 35% of patients who received hypo-fractionated radiotherapy combined with the anti-PD-1 monoclonal antibody regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective study assessed a combination of RT and ICI therapy in AM patients who did not respond to anti-PD-1 monotherapy. The abscopal effect could be induced in 38% of the patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was a monocenter retrospective analysis of data prospectively collected according to previously published procedures [ 19 , 20 ] in our referral skin cancer department for anti-PD-1 mAb-treated melanoma patients not included in double-blinded trials. Nivolumab or pembrolizumab was infused intravenously according to product labels until unambiguous progressive disease (PD), unacceptable AE, or decision to discontinue treatment, but was continued beyond progression at first evaluation to allow for pseudo-progression [ 22 ], or later if ≥1 lesion could be treated locally.…”
Section: Methodsmentioning
confidence: 99%
“…Hypofractionated RT delivers higher doses per session than standard palliative RT and requires a reduced number of sessions. We previously reported that hypofractionated RT combined with an unmodified anti-PD-1 mAb monotherapy regimen induced long-lasting efficacy, with a CR+PR rate of 36–38% in melanoma patients who either received this combination early [ 19 ] because of life-threatening metastases or had previously failed anti-PD-1 monotherapy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%